Pengaruh Pembelajaran Discovery Learning Terhadap Kemandirian Belajar Dan Pemahaman Siswa Pada Materi Akuntansi Kelas X Di Smkn 1 Kamal - Purwantiningsih, Anis Tri; Tri Eka Silver, Soesiana; Muhajir (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2024)
This study was conducted to determine effect of discovery learning model on learning independence and student understanding of basic accounting equation material in class X accounting and finance at SMKN 1 Kamal. Study used quantitative assessment with questionnaire research instruments and test questions. Using population 49 students with samples, class X AKL-1 (24 students), class X AKL-2 (23 students). Sampling using nonprobability sampling method with saturated sampling technique. Data processing uses IBM SPSS v.21 for windows application with analysis method of validity test, homogeneity test, normality test, independent sample T-test test and, multivariate analysis of variance test or manova test. Testing independent sample T-test test, data obtained first hypothesis sig value. 0.003 <0.05, meaning effect discovery learning model on learning independence in basic accounting equations lesson of class X AKL SMKN 1 Kamal students, second hypothesis obtained data sig value. 0.000 <0.05, meaning effect discovery learning model on student understanding of basic accounting equations in class X AKL students of SMKN 1 Kamal. Last result, multivariate analysis of variance (Manova) test obtained sig value data. 0.000 <0.05, meaning effect discovery learning model on learning independence and student understanding in basic accounting equation class X AKL SMKN 1 Kamal. Conclusion, there is effect of discovery learning model on students' understanding in basic accounting equation subject of class X AKL SMKN 1 Kamal. Learning using discovery learning model is considered effective in increasing students' learning independence and understanding in basic accounting equation subject of class X accounting and finance of SMKN 1 Kamal